Recessive LAMA5 Variants Associated With Partial Epilepsy and Spasms in Infancy - Luo, Sheng; Liu, Zhi-Gang; Wang, Juan; Luo, Jun-Xia; Ye, Xing-Guang; Li, Xin; Zhai, Qiong-Xiang; Liu, Xiao-Rong; Wang, Jie; Gao, Liang-Di; Liu, Fu-Li; Ye, Zi-Long; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective The LAMA5 gene encodes the laminin subunit α5, the most abundant laminin α subunit in the human brain. It forms heterotrimers with the subunit β1/β2 and γ1/γ3 and regulates neurodevelopmental processes. Genes encoding subunits of the laminin heterotrimers containing subunit α5 have been reported to be associated with human diseases. Among LAMAs encoding the laminin α subunit, LAMA1-4 have also been reported to be associated with human disease. In this study, we investigated the association between LAMA5 and epilepsy. Methods Trios-based whole-exome sequencing was performed in a cohort of 118 infants suffering from focal seizures with or without spasms. Protein modeling was used to assess the damaging effects of variations. The LAMAs expression was analyzed with data from the GTEX and VarCards databases. Results Six pairs of compound heterozygous missense variants in LAMA5 were identified in six unrelated patients. All affected individuals suffered from focal seizures with mild developmental delay and three patients presented also spasms. These variants had no or low allele frequencies in controls and presented statistically higher frequency in the case-cohort than controls. Protein modeling showed that at least one variant in each pair of biallelic mutation affected hydrogen bonds with surrounding amino acids. Among the biallelic mutations in cases with only focal seizures, two variants of each pair were located in different structural domains or domains/links, whereas in the cases with spasms, the biallelic mutations were constituted by two variants in the identical functional domains or both with hydrogen bond changes. Conclusion LAMA5 gene was potentially a causative gene of infant epilepsy. The establishment of the association between LAMA5 and epilepsy will facilitate the genetic diagnosis and management in patients with infant epilepsy.